2019
DOI: 10.1002/jcp.28383
|View full text |Cite
|
Sign up to set email alerts
|

Small regulatory polypeptide of amino acid response negatively relates to poor prognosis and controls hepatocellular carcinoma progression via regulating microRNA‐5581‐3p/human cardiolipin synthase 1

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies with extremely high rates of occurrence and death. Long noncoding RNAs (lncRNAs) have been increasingly revealed to participate in tumorigenesis and development of multiple human cancers, including HCC. LINC00961 is a novel lncRNA which has been uncovered as a tumor suppressor in lung cancer and glioma. However, the role of LINC00961 in HCC has never been probed yet. Herein, we revealed a marked downregulation of LINC00961 in HCC tissues and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Available data showed that overexpression of miR-5581-3p promoted cellular activities in hepatocellular carcinoma by inhibiting cardiolipin synthase 1. 26 This study supplemented the knowledge regarding the physiological function of hsa-miR-5581-3p.…”
Section: F8 Is a Target Gene Of Hsa-mir-5581-3p And Hsa-mir-mentioning
confidence: 69%
“…Available data showed that overexpression of miR-5581-3p promoted cellular activities in hepatocellular carcinoma by inhibiting cardiolipin synthase 1. 26 This study supplemented the knowledge regarding the physiological function of hsa-miR-5581-3p.…”
Section: F8 Is a Target Gene Of Hsa-mir-5581-3p And Hsa-mir-mentioning
confidence: 69%
“…Mechanistically, in HepG2 and Hep3B HCC cell lines, overexpression of long non-coding RNA LINC00961 was proportionally correlated with CRLS1 mRNA and protein overexpression, resulting in the inhibition of HCC progression (i.e., inhibition of cell proliferation, migration, and invasion in HCC cells). Both LINC00961 and CRLS1 protein expression were downregulated in patients' HCC tumors [41]. These studies suggest a tumor suppressor function for CRLS1 that is co-expressed with other tumor suppressor proteins.…”
Section: Cardiolipin Metabolismmentioning
confidence: 70%
“…More studies also propose the tumor suppressor activity of CRLS1 in HCC. It has been found that LINC00961, a novel long non-coding RNA which has been uncovered as a tumor suppressor in lung cancer and glioma, was downregulated in HCC tissues and cell lines (HepG2 and Hep3B) [41]. Mechanistically, in HepG2 and Hep3B HCC cell lines, overexpression of long non-coding RNA LINC00961 was proportionally correlated with CRLS1 mRNA and protein overexpression, resulting in the inhibition of HCC progression (i.e., inhibition of cell proliferation, migration, and invasion in HCC cells).…”
Section: Cardiolipin Metabolismmentioning
confidence: 99%
“…We showed miR-5581-3p was a target of LINC00526 through bioinformatic analysis, luciferase activity assay, and RIP assay. miR-5581-3p was previously found to be negatively regulated by LINC00961 in hepatocellular carcinoma and thus affect cancer progression [12]. Subsequently, BEX1 was confirmed as a target of miR-5581-3p in glioma.…”
Section: Discussionmentioning
confidence: 94%